Analisis Prosedur Pemanggilan Para Pihak yang Bersengketa - Mukharomah, Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The procedure for summoning the parties to the dispute is one of the important stages in the legal process. This invitation aims to inform the parties involved about the time, place and agenda of the conference so that they can prepare themselves to attend the process. This article discusses in detail the steps that must be taken in a summons, starting from preparing the summons letter, delivery method, to receiving it by the contacted party. Apart from that, various legal threats are also explained if one of the parties does not comply with the summons, including possible legal sanctions and the impact on broadcasting. By understanding this procedure, it is hoped that the parties to the dispute will be better prepared and cooperative in facing the legal process, and can avoid negative consequences due to their absence.